A generalized maximum entropy stochastic frontier measuring productivity accounting for spatial dependency - Tonini, Axel; Pede, Valerien (MDPI, 2011)
In this paper, a stochastic frontier model accounting for spatial dependency is developed using generalized maximum entropy estimation. An application is made for measuring total factor productivity in European agriculture. The empirical results show that agricultural productivity growth in Europe is driven by upward movements of technology over time through technological developments. Results are then compared for a situation in which spatial dependency in the technical inefficiency effects is not accounted.